Valg af ord til en islandsk fremmedordbog - Kvaran, Guðrún (Nordiske Studier i Leksikografi, 2010)
No Icelandic dictionaries, neither old nor new, deal with loan words in the Icelandic language as a part of the vocabulary, mainly because most words of that kind have not been accepted in the language by the general public. Of course one can find in the books some of the most commonly used words, but often with a negative comment. For some time I have been collecting loan words from 1850 till this day as a preparation for an Icelandic dictionary of loan words. As was to be expected, there have arisen several questions about what words should be treated in a book like this and which should be left out. One of the most difficult questions was if I should distinguish between loan words and foreign words, as is done in the Scandinavian languages and in German. I came to the conclusion that it would serve the purpose better to deal with both groups of words as one group as that is what people are used to in Iceland. In chapter two of this paper I discuss the common differences between loan words, foreign words and assimilated words. From there I go in chapter three over to the problem of choosing words for the first Icelandic dictionary of loan words. In the last chapter I show examples from the database Lexa which I use for my purpose.